2020
DOI: 10.1021/acsaem.0c01177
|View full text |Cite
|
Sign up to set email alerts
|

A Ternary-Mixture-Based Counter Electrode for Quantum-Dot-Sensitized Solar Cells

Abstract: A ternary mixture of carbon, copper sulfide, and cobalt sulfide was used to fabricate the counter electrode (CE) in quantum-dot-sensitized solar cells (QDSSCs). The ternary-mixture-based CE achieved much higher energy conversion efficiency than any CE based on the individual material. The mixture and the CE were investigated by photocurrent density–voltage characteristics, X-ray diffraction patterns, electrochemical impedance spectroscopy, and contour line plots. A balanced mix results in enhanced photocurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The counter electrode (CE) is an essential component in QDSSCs for the following reasons: 1) it catalyzes the reduction reaction of the oxidized species present in the electrolyte, 2) collects electrons from the electrical circuit and transfers them to the electrolyte, thus promoting the reduction of oxidized species, 3) ensures the flow of electrons in the photoelectrochemical solar cell [117][118][119] Therefore, the CE must have high catalytic activity in the electrolyte used in the QDSSCs, high electrical conductivity, good adhesion to the substrate, low cost, and high stability. [120][121][122] Early in the development of the QDSSCs it was observed that most chalcogenide QDs were unstable in the iodide/triiodide electrolyte.…”
Section: Ces In Qdsscsmentioning
confidence: 99%
See 1 more Smart Citation
“…The counter electrode (CE) is an essential component in QDSSCs for the following reasons: 1) it catalyzes the reduction reaction of the oxidized species present in the electrolyte, 2) collects electrons from the electrical circuit and transfers them to the electrolyte, thus promoting the reduction of oxidized species, 3) ensures the flow of electrons in the photoelectrochemical solar cell [117][118][119] Therefore, the CE must have high catalytic activity in the electrolyte used in the QDSSCs, high electrical conductivity, good adhesion to the substrate, low cost, and high stability. [120][121][122] Early in the development of the QDSSCs it was observed that most chalcogenide QDs were unstable in the iodide/triiodide electrolyte.…”
Section: Ces In Qdsscsmentioning
confidence: 99%
“…[160][161][162] Composite CEs have demonstrated greater efficiency in QDSSCs, due to the synergistic combination between a material with high catalytic activity, such as metal sulfide, combined with a material with high electrical conductivity, high surface area, and high stability in the polysulfide electrolyte, such as carbon-based materials. [121] Li et al [117] demonstrated the preparation of a low-cost ternary composite with copper sulfide, cobalt sulfide, and carbon for application as a counter electrode in QDSSC. The synergistic effect between the three components was demonstrated, showing better performance when a balanced composition was used, 1:1:1 wt%, compared to other simple or binary combinations of materials.…”
Section: Composite Carbon-based Cementioning
confidence: 99%
“…Redox impedance at the electrolyte/ CE interface induces a smaller semicircle in the high-frequency region, while impedance at the photoanode/ electrolyte interface induces a larger semicircle in the mid-frequency region. Symbols in the equivalent circuit represent, the series resistance (Rs), charge transfer resistance (R 1 ct) and chemical capacitance (CPE 1 ) at the electrolyte/ CE interface, and, charge transfer resistance (R 2 ct) and chemical capacitance (CPE 2 ) at the photoanode/ electrolyte interface (Dissanayake et al, 2021a and2021b;Li et al, 2020). According to the estimated EIS parameters mentioned in Table 2, S 2 QDSSC show slightly improved Rs due to increased photogenerated electrons flowing in the system.…”
Section: Eis Characterizationmentioning
confidence: 99%
“…The sulfide/polysulfide redox couple has been intensively investigated in QD photovoltaics because of its perfect stabilization effects on QD nanocrystals, and suitable energy level matching with QD nanocrystals. , One of the main functions of a photocathode is to highly catalyze the sulfide/polysulfide redox (i.e., S n 2– to S 2– ) at the interface of catalyst/electrolyte. , It is well-known that the catalysts on the photocathode have a significant impact on the final PCE of QD photovoltaics. Thus, the desirable catalysts are expected to have the merits of excellent electrical conductivity, high chemical stability in the polysulfide electrolyte, and perfect catalytic performance toward the polysulfide redox reduction (SRR) reaction. However, the conventional Pt is not active for SRR because the sulfur species could coordinate with Pt . The adverse effect led to a low PCE for QD photovoltaics …”
mentioning
confidence: 99%
“… , Furthermore, compared with the N-C sample (78.16 m 2 /g), the Fe-N-C sample exhibited an enhanced BET specific surface area (509.44 m 2 /g) (Figure S4 and Table S1), which could arise from the decomposition of Fe precursor during the high temperature pyrolysis. It also indicated that the introduction of Fe precursor during the synthesis process could adjust the pore structure of the final samples. More importantly, the enhanced BET surface area would be favorable for the interaction with the S 2– /S n 2– redox couple in the catalytic process. (See the Supporting Information for the detailed discussions on XPS and BET measurements. )…”
mentioning
confidence: 99%